Stabilization of Tangent and Normal Contact Forces for a Quadrotor subject to Disturbances - Izaguirre-Espinosa, C.; Munoz-Vazquez, A.; Sanchez-Orta, A.; Parra-Vega, V.; Garcia-Rodriguez, R.; Castillo, P.; Arreguin-Jasso, D. (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2022)
Force exertion, object manipulation, and interaction are novel trending research topics of autonomous flying robots that can yield hoovering. Moreover, specifically with quadrotors, the vibration caused by the high natural frequency of rotating propellers exacerbates the problem of maintaining contact and exerting force against a rigidly fixed object. This contact vibration transfers back kinetic energy to the quadrotor that, in worst-case scenarios, surpasses its flying capabilities, which may lead to a crash. This paper studies the problem of aerial contact stabilization of a quadrotor equipped with a hemispherical deformable tip, which accommodates contact forces at a lower frequency. Thus two phenomena not studied in the literature arise: the rolling motion, and the deformation at contact. The contact force stabilization restores the effects of deformation while simultaneously endowing rolling by controlling a tangent constrained force. A model-free continuous attitude fractional controller to guarantee finite-time attitude stabilization is proposed. The residual coupled nonlinear dynamics yields the desired attitude corresponding to a given contact force; thus, force stabilization is achieved. Finally, experimental results are presented to assess the performance of the proposed approach.